Chiral Near‐Infrared Fluorophores by Self‐Promoted Oxidative Coupling of Cationic Helicenes with Amines/Enamines. Issue 16 (8th March 2021) - Bosson, Johann; Labrador, Geraldine M.; Besnard, Céline; Jacquemin, Denis; Lacour, Jérôme
Abstract: In one pot, tertiary alkyl amines are oxidized to enamines by cationic dioxa[6]helicene, which further reacts as electrophile and oxidant to form mono or bis donor‐π‐acceptor coupling products. This original and convergent synthetic approach provides a strong extension of conjugation yielding chromophores that absorb intensively in far‐red or NIR domains ( λ max up to 791 nm) and fluoresce in the NIR as well ( λ max up to 887 nm). Intense ECD properties around 790 nm with a |Δ ϵ | value up to 60 M −1 cm −1 are observed. Abstract : Cationic dioxa[6]helicene oxidizes alkyl amines to enamines and further reacts in situ as an electrophile to form, in one‐pot multi‐step cascades, fully delocalized mono or bis donor‐π‐acceptor coupling products. This original approach provides chiral cyanine‐like chromophores that absorb up to the NIR and fluoresce alike, with intense NIR ECD (Δ ϵ up to 60 M −1 cm −1 ). DFT showcases the importance of conformers in the strong chiroptical response.